NEED ANALYSIS IN THE INTEGRATION OF SDGs IN ENGLISH FOR PUBLIC ADMINISTRATION - Kristining Seva; Asnita Sirait; Budi Setiandari (XXXXXXXX, 2024)
This study is designed to investigate the students' needs on English for Specific Purposes (ESP)  for students at Parahyangan Catholic University (UNPAR), majoring Public Administration (PA). This study is conducted on two reasons: first, the great demand of active  communication in English; second; the students' inability in implementing their knowledge about Sustainable Development Goals (SDGs) in language skills. Therefore, this study will be guided by two basic research questions which led to identifying the students' needs towards  part of SDGs based material given in English class, and what kind of activities are appropriate  for improving their language skills. The data-led investigation into students' needs on the selection, presentation, and evaluation of the material concerning their orientation and preferred classroom activities. The appropriateness of the materials was also revealed as the basis for the necessary revisions for the existing materials. This design research is based on a descriptive qualitative study that will investigate the PA  students, PA lecturers, and the stakeholders. The procedure to collect the data was through questionnaires and interviews to clarify some raw data. The appropriate textbook used in the previous classroom will also be part of the data collection to find out the necessary materials. The findings will be used as guidance to design a suggested syllabus with some learning activities with the expectation to improve the student's language skills. The suggestions for ESP educators were also elaborated in this study.